2004
DOI: 10.1002/nme.1075
|View full text |Cite
|
Sign up to set email alerts
|

Finite element formulations of strain gradient theory for microstructures and the C0–1 patch test

Abstract: SUMMARYBased on finite element formulations for the strain gradient theory of microstructures, a convergence criterion for the C 0-1 patch test is introduced, and a new approach to devise strain gradient finite elements that can pass the C 0-1 patch test is proposed. The displacement functions of several plane triangular elements, which satisfy the C 0 continuity and weak C 1 continuity conditions are evaluated by the C 0-1 patch test. The difference between the proposed C 0-1 patch test and the C 0 constant s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
3

Year Published

2006
2006
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 22 publications
0
37
0
3
Order By: Relevance
“…However, a strict C 1 element is complicated to construct and implement. Alternatively, Soh and Chen [26] advocated using two types of displacement functions with same nodal parameters: one satisfies C 0 continuity and quadratic completeness to calculate first derivatives of displacement, and the other satisfies C 1 weak continuity to calculate second derivatives of displacement. This approach has been used to develop an effective 18-DOF plane couple stress/strain gradient triangular element [26].…”
Section: A Weak Continuity Condition Of Axisymmetric Element For Coupmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a strict C 1 element is complicated to construct and implement. Alternatively, Soh and Chen [26] advocated using two types of displacement functions with same nodal parameters: one satisfies C 0 continuity and quadratic completeness to calculate first derivatives of displacement, and the other satisfies C 1 weak continuity to calculate second derivatives of displacement. This approach has been used to develop an effective 18-DOF plane couple stress/strain gradient triangular element [26].…”
Section: A Weak Continuity Condition Of Axisymmetric Element For Coupmentioning
confidence: 99%
“…Soh and Chen [26] established the C 0 À 1 patch test for the finite element analysis of couple stress/strain gradient theory. It can be summarized as follows.…”
Section: Numerical Examplesmentioning
confidence: 99%
“…In other words, the displacement function of the patch test has to be a complete quadratic function which satisfies the equilibrium equation. In the papers [15,16] , the authors proposed the enhanced C 0-1 patch test condition for the couple stress/strain gradient theory and established an 18-parameter triangular element that satisfies the C 0-1 patch test condition.…”
Section: -1 Patch Test For the Couple Stress/strain Gradient Theorymentioning
confidence: 99%
“…Therefore, the above mentioned obstacles in the patch test still exist. In the papers [15,16] , further discussion of the patch test found that the element for couple stress/strain gradient problem was not able to pass the constant curvature C 1 patch test. Because the test function which described constant strain curvature of the strain gradient theory cannot pass the C 0 patch test in state of the constant membrane stresses, the C 0-1 patch test is the test of linear membrane stress and constant strain curvature for the strain gradient theory/couple stress theory, but not both of constant stresses.…”
Section: Introductionmentioning
confidence: 98%
“…[6,7], the authors further studied the patch test for micro couple stress/strain gradient element. They proposed the enhanced C 0−1 patch test and established C 0−1 triangular elements with 18 parameters.…”
mentioning
confidence: 99%